The Influence of Political Connections on Banking Performance with Board of Directors Diversity as a Moderating Variable - Putriani, Eva; Midiastuty, Pratana Puspa; Suranta, Eddy; Putra, Danang Adi (Yayasan Ilomata, 2024)
The study endeavors to empirically demonstrate how political ties impact the performance of banks, while considering the Board of Directors' diversity as a potential influencing factor among banking firms listed on the Indonesia Stock Exchange during the 2017-2022 period. Within this research, political connections are represented as dummy variables, denoting firms linked with the government, directors having affiliations with shareholders, or associations with political parties or other governmental bodies. Banking performance is assessed through proxies such as ROA, ROE and loan loss provision. The diversity of the board of directors, evaluated by the ratio of female directors to the total board members, serves as a moderating variable. The research formulates two hypotheses, all of which underwent testing using the SPSS 28 application. Findings revealed that political connections positively influence banking performance as measured by ROA, demonstrate no impact on ROE, and exhibit a significant negative effect on LLP. Moreover, the diversity of the board of directors moderates the correlation between political connections and banking performance in terms of ROA and ROE, while it does not moderate this relationship concerning LLP. The implication of this research is based on the theory of resource dependence where political connections owned by banks provide benefits to firm in the form of easy market access and are able to reduce banking performance in the form of decreasing bad debts. These findings might prompt future regulators to contemplate regulations concerning gender diversity within board compositions, considering its potential implications for governance and performance.